2020
DOI: 10.1016/j.jid.2019.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CCN3 in Systemic Sclerosis Endothelial Cells Contributes to Impaired Angiogenesis

Abstract: Systemic sclerosis (SSc) is a rare and severe connective tissue disease combining autoimmune and vasculopathy features, ultimately leading to organ fibrosis. Impaired angiogenesis is an often silent and life-threatening complication of the disease. We hypothesize that CCN3, a member of the CCN family of extracellular matrix proteins, which is an antagonist of the profibrotic protein CCN2 as well as a proangiogenic factor, is implicated in SSc pathophysiology. We performed skin biopsies on 26 patients with SSc,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Due to technical difficulty in isolation and culture of human dermal microvascular endothelial cells (HDMECs), 19‐22 currently immunohistochemistry in skin tissue 23,24 and human umbilical vein endothelial cells 25,26 are major approaches in the study of pathogenesis of psoriasis. In the present study, we isolated HDMECs from the human dermis and compared the functions, including angiogenesis, migration and metabolism, of HDMECs from psoriatic lesions vs. that from the skin of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Due to technical difficulty in isolation and culture of human dermal microvascular endothelial cells (HDMECs), 19‐22 currently immunohistochemistry in skin tissue 23,24 and human umbilical vein endothelial cells 25,26 are major approaches in the study of pathogenesis of psoriasis. In the present study, we isolated HDMECs from the human dermis and compared the functions, including angiogenesis, migration and metabolism, of HDMECs from psoriatic lesions vs. that from the skin of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, studying SSc epidermis and especially pigmentary changes may help to detect other early manifestations in SSc. CCN protein dysregulation, as evidenced here for CCN3 in pigmentation and recently in vasculopathy (Henrot, Moisan, Laurent, et al, 2020), may provide a mechanistic link between vasculopathy, sclerosis, and Left panel, SSc patient, early disease (duration <1 year). Right, SSc patient, advanced disease (duration 6 years).…”
Section: Musculoskeletal Involvementmentioning
confidence: 64%
“…Among secreted factors that could explain this association, the protein CCN3 (NOV) is a promising candidate to study, being associated with both angiogenesis (Henrot, Moisan, Laurent, et al, 2020) and epidermal pigmentation regulation (Fukunaga-Kalabis et al, 2006;Ricard et al, 2012). Thus, we decided to study SSc epidermis, in patients presenting or not pigmentary changes, with a special focus on CCN3 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In brightfield images, we observed a striking pattern of dark brown pigment deposit in the dermis of eight patients with SSc, particularly lining dermal vessels. We could not easily evidence any pigmented deposit in the superficial dermis as its thickness was greatly reduced (Henrot et al, 2020). CD31 staining allowing the identification of endothelial cells confirmed that pigment was specifically located near the outside layer of dermal vessels (Figure 1b).…”
Section: Is Hyperpigmentation In Systemic Sclerosis a Perivascular Dementioning
confidence: 94%